The role of melting dead ice on landscape transformation in the early Holocene in Tuchola Pinewoods, North Poland. (19th November 2015) - Słowiński, Michał; Błaszkiewicz, Mirosław; Brauer, Achim; Noryśkiewicz, Bożena; Ott, Florian; Tyszkowski, Sebastian
Abstract: On the basis of macrofossil and pollen analyses, AMS 14 C-dating, and geomorphological investigations, we reconstructed the development of hydrological changes during the Lateglacial to early Holocene transition in Tuchola Pinewoods (Bory Tucholskie) in northern Poland. In this region, the Wda River flows in polygenetic valleys, typical for the young glacial landscape of the northern central European lowlands. The middle section of this river provides a suitable setting to demonstrate the environmental and hydrological changes in the Late Glacial and early Holocene, because (1) it is a small and well-defined area and (2) the existence of a morphologically preserved river valley from late glacial period. In this study, we focused on a short terrestrial sediment core (48 cm) that represents four phases of landscape evolution during the early Holocene: telmatic, lacustrine, lacustrine-fluvial and alluvial. Abrupt changes in lithology and sediment structures exhibit rapid changes and threshold processes in environmental conditions. The AMS 14 C dating of terrestrial plant remains revealed an age for the basal sediments of 11 223 ± 23 cal BP and thus falls within the Preboreal biozone. Plant macrofossil indicators provide evidence of water level and edaphic changes in the basin. The results of our study demonstrate a strong influence of melting buried ice blocks on the geomorphological development, hydrological changes in the catchment, and the biotic environment in the early Holocene.